THE RELATIONSHIP BETWEEN LEADERSHIP, COMPENSATION, AND COMPETENCE WITH EMPLOYEE’S PERFORMANCE - Nurlaila Nurlaila (Indonesian Journal of Multidisciplinary Science, 2023)
Employee performance is one of the important factors in the success of an organization or company. So that to achieve optimal performance, there are several factors that can influence it, including leadership, compensation, and employee competence. This study aims to determine the relationship of leadership, compensation and competence to employee performance. This research is included in the type of quantitative research, while the data collection technique is done by questionnaire and literature study. The research object in this study were employees of PT Benua Integrasi Global. The results showed that leadership, compensation, and employee competence have a relationship with employee performance. Good leadership can provide clear direction and motivate employees to work better. Meanwhile, compensation that is fair and in accordance with employee contributions can increase employee satisfaction and motivation at work. In addition, adequate and continuously developed employee competencies can also affect the performance of PT Benua Integrasi Global employees.